Design hygrothermally functional wooden insulation systems: A parametric study for mixed climate. (January 2023) - Zhao, Mosha; Künzel, Hartwig M.; Mehra, Schew-Ram
According to existing measurements and simulation results, the indoor thermal comfort in traditional wooden buildings (still remaining in a large amount) in the Chinese Hot-Summer-Cold-Winter zone is very poor in winter. However, few studies can be found regarding the energy retrofitting of their wooden enclosures, which is increasingly regarded as essential for improving indoor thermal comfort and maintaining built heritage. Therefore, this study demonstrates a method based on parametric study applying the widely validated WUFI ® Plus software to help design hygrothermally functional insulation systems for this area. The parametric study was conducted on the example of traditional exterior wooden walls in Tongren in southern China. Five parameters were investigated, including internal and external insulation systems, vapor-open (mineral wool) and vapor-tight (XPS) insulation materials, a U-value of 0.8 W/(m 2 K) as well as a lower U-value of 0.24 W/(m 2 K) for the insulated walls, different capabilities and positions of an additional vapor control layer, as well as different cooling/dehumidification conditions in the warm period of a year. It has been found in this study that, if possible, a lower U-value than the current Chinese design standard for energy efficiency of buildings (0.8 W/(m 2 K) should be preferred for energy retrofitting. This can limit the yearly duration of a high internal surface relative humidity over 80% shorter than 30 days without any dehumidification devices. Besides, this study provides some feasible wall configurations with instructions on their limitations to guide future work regarding the design of insulated building components and the operation of renovated traditional wooden buildings.